Porous liquid metal-organic frameworks with selectively high gas solubility. (15th July 2023) - Ma, Jie; He, Libo; Yang, Ruilu; Wang, Dechao; Qu, Danyao; Su, Chen; Pang, Haili; Wu, Weiwei; Li, Peipei; Zhang, Lu; Liu, Xiaowei
Graphical abstract: Highlights: A novel kind of porous liquid, i.e., UIO-66-PL, was fabricated through wet-impregnation method. UIO-66-PL with well-maintained porosity was stable at room temperature. UIO-66-PL could function as a kind of fluid selective gas sorbent with high target gas solubility. Abstract: Porous liquid metal–organic frameworks (MOFs) have recently been discovered rather promising for gas absorption and separation in practical chemical industry processes. In this work, we successfully fabricated a kind of MOF-based porous liquid (i.e., UIO-66-PL) by dispersing the hydrophilic porous filler of UIO-66-NH2 nanoparticles into a specific hydrophilic ionic liquid (IL, [HEMIM][DCA]) through the wet-impregnation method. The obtained UIO-66-PL was a kind of stable porous liquid with well-maintained permanent porosity and liquid-like behavior at room temperature. More importantly, this UIO-66-PL has larger gas absorption capacities than its reference IL hindered solvent as the well-preserved permanent porosity could act as free void space for gas accommodation. Also, IL could serve as a selective gate for target gas to the permanent porosity within UIO-66-PL, i.e., the majority of the permanent porosity in UIO-66-PL is inaccessible to nitrogen, but available for carbon dioxide, demonstrating that this UIO-66-PL could function as a type of fluid selective gas sorbent with high target gas solubility.